Structures, Not Strings: Linguistics as Part of the Cognitive Sciences. Issue 12 (December 2015) - Everaert, Martin B.H.; Huybregts, Marinus A.C.; Chomsky, Noam; Berwick, Robert C.; Bolhuis, Johan J.
Abstract : There are many questions one can ask about human language: its distinctive properties, neural representation, characteristic uses including use in communicative contexts, variation, growth in the individual, and origin. Every such inquiry is guided by some concept of what 'language' is. Sharpening the core question – what is language? – and paying close attention to the basic property of the language faculty and its biological foundations makes it clear how linguistics is firmly positioned within the cognitive sciences. Here we will show how recent developments in generative grammar, taking language as a computational cognitive mechanism seriously, allow us to address issues left unexplained in the increasingly popular surface-oriented approaches to language. Trends: The computations of the mind rely on the structural organization of phrases but are blind to the linear organization of words that are articulated and perceived by input and output systems at the sensorimotor interface (speech/sign). The computational procedure that is universally adopted is computationally much more complex than an alternative that relies on linear order. Linear order is not available to the systems of syntax and semantics. It is an ancillary feature of language, probably a reflex of properties of the sensorimotor system that requires it for externalization, and constrained by conditions imposed by sensorimotor modalities. It follows that language is primarily an instrument for the expression of thought. Language is neither speech/sign (externalized expression) nor communication (one of its many possible uses).